Palliative Care Education to Enhance Informal Caregivers’ Skills in Caring for Patients with Cancer: A Scoping Review - Effendy, Christantie; Kurianto, Endar; Darmayanti, Anisa Rayu Ike; Noviana, Uki; Nurjannah, Intansari (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: Living with cancer causes stress for both patients and caregivers. Empowering family caregivers is critical in palliative care. It is well known that a lack of proper knowledge and training of informal caregivers is a barrier to palliative care provision at home. AIM: This scoping review aimed to explore palliative care education to enhance informal caregiver skills in caring for a cancer patient. METHODS: A scoping literature review was conducted with systematic searches in multiple databases – PubMed, Cochrane, PsycINFO, and SCOPUS (2000–2021). Studies were selected based on programs content and its impact evaluation. RESULTS: The remaining 181 citations were examined at full-text level; 173 studies did not meet inclusion criteria, yielding eight included papers. Four papers focused on palliative care educational programs for family caregivers, and four papers included patients and caregivers. There was a diverse variation in the mode of delivery and duration of educational input. The programs offered an insight into the main elements of working with individuals in a palliative care bundle. Most studies reported participants improved their knowledge, self-efficacy, and competency and prepared for their roles. CONCLUSION: The findings show the need for family caregivers for more regular and reliable palliative education programs. Randomized controlled trials with rigorous randomization processes, more significant sample numbers and more appropriate control groups focused explicitly on caregiver education may improve the evidence. © 2022 Christantie Effendy, Endar Kurianto, Anisa Rayu Ike Darmayanti, Uki Noviana, Intansari Nurjannah.